A Qualitative Research on Identifying the Exposure and Risk Perceptions of Healthcare Workers who are Diagnosed with COVID-19 - Remzi Altunışık; Emel Yılmaz; Oğuz Karabay (Sakarya Tıp Dergisi, 2022)
Objective: In this study, it’s aimed to examine biological and psychosocial risk perceptions, and expectations of life after treatment of the healthcare personnel who were diagnosed as covid-19 positive while working at the pandemic hospital and resumed after their treatments. Materials and Methods: In line with the purpose of the study, a case study method was adopted in the qualitative research approach. Among the purposive sampling methods, maximum diversity sampling is used for the sample of the study that is 13 healthcare workers working in different units and levels who have worked in the pandemic period. As the data collection tool, semi-structured form was used, and the data obtained through interview questions were transcribed word-by-word and analyzed using the content analysis technique using the Maxqda program. Results : The most common theme during the pandemic is “worry” which is a subcode of “negative feelings” under the “psychological factors” theme and the second most common dimension is “family” code under the theme of “social factors”. Conclusion: Even though some of the employees were working at the pandemic hospital, the belief that the risk of coronavirus infection was low to them was the most striking subject in the research process. This situation has been examined from the perspective of unrealistic optimism theory. It is explained by the assumption that information processing errors are made about the risks of the work or the tendency to deny the risk to reduce anxiety. Although the studies carried out in both aspects provide temporary relief for individuals, we think that the increase in this situation may reduce the behavior of taking measures against risks in individuals.